The nexus clause: A peculiarly Australian obstacle - Zachary Gorman (Cogent Arts & Humanities, 2018)
The nexus between the House of Representatives and the Senate as set out in Section 24 of the Australian Constitution states that the Senate be half the size of the House of Representatives. It was a constitutional provision without precedent, the only such clause in the Australian Constitution. Little work has been done on the nexus. This paper examines how it came into existence during the Constitutional Conventions largely as the consequence of two desires. One was to protect the power of the Senate and the place of the smaller states. The other was to prevent the overexpansion of the House of Representatives. The paper then considers the first expansion of the House of Representatives in 1949 and the unsuccessful attempt, begun by Robert Menzies, to abolish the nexus in 1967 despite overwhelming support by the major political parties.